Analisis Pengaruh Struktur Modal, Investasi Baru dan Perputaran Persediaan terhadap Profitabilitas - Kusprianti, Riska Fitria; Saleh, Dean Subhan; Hadi, Yulianto (The Double Entry Journal, 2022)
The purpose of this research is to analyze the composition of capital structure, new investment and assessment of profitability. This study uses a sample of 13 companies incorporated in the automotive subsector which are listed on the Indonesia Stock Exchange in 2015-2017. The analytical method used is multiple linear regression analysis with eviews 9. The results indicates that capital structure, investment structures and inventory turnover signi profitability. While the capital structure, new investment and turnover variables are not significant to profitability.